Long-term follow-up of an attenuated presentation of NAXE-related disease, a potentially actionable neurometabolic disease: a case report - Almudhry, Montaha; Prasad, Chitra; Rupar, C. Anthony; Tay, Keng Yeow; Prasad, Asuri N. (Frontiers in Neurology, 2024)
Background: Early-onset progressive encephalopathy with brain edema and/or leukoencephalopathy (PEBEL-1) is an autosomal recessive disorder where a fluctuating clinical course is exacerbated by febrile illnesses. Pathogenic NAD(P)HX epimerase (NAXE) gene mutations underpin this disorder. This mutation damages the metabolite repair system involved in regenerating crucial redox carriers.Longer survival has rarely been reported in this potentially actionable entity.Objectives: This case study aimed to report a milder phenotype of a patient with NAXE gene mutation and his longitudinal follow-up of more than 20 years.A 24-year-old male became symptomatic in infancy with frequent initial neurological decompensations in the setting of infections with subsequent clinical improvement followed by stability with residual cerebellar dysfunction. Clinical features noted over the years include chronic ataxia, nystagmus, ptosis, mild spasticity of lower limbs, and neuropsychiatric symptoms. Cerebellar and spinal cord atrophy were noted on cranial and spinal MR imaging. Biallelic homozygous variants in the NAXE gene (c.733 A>C) were identified on whole exome sequencing. Symptom management included initiation of a mitochondrial cocktail with carnitine, coenzyme Q, and thiamine. Subsequently, niacin (Vitamin B3), which is involved in the cellular biosynthesis of NAD+, was added, given its potentially beneficial therapeutic impact.